Green eggs and ham : dr. seuss - Seuss, Dr. (Collins London, 2002)
With a rhyming vocabulary of only 50 words, this hilarious book tells the story of Sam-I-Am$1 (Bs relentless pursuit of a grumpy individual who refuses to eat a plate of green eggs and ham.s